Rural telephony: The community call boxt - Jerling, Dion (Technical Centre for Agricultural and Rural Cooperation, 2008)
A pilot project to introduce payphones, connected to satellite networks, is providing telephone services to remote communities and helping to develop the telecoms market in Zambia.